Angioedema Without Wheals: Challenges in Laboratorial Diagnosis - Grumach, Anete S.; Veronez, Camila L.; Csuka, Dorottya; Farkas, Henriette (Frontiers in Immunology, 2021)
Angioedema is a prevailing symptom in different diseases, frequently occurring in the presence of urticaria. Recurrent angioedema without urticaria (AE) can be hereditary (HAE) and acquired (AAE) and several subtypes can be distinguished, although clinical presentation is quite similar in some of them. They present with subcutaneous and mucosal swellings, affecting extremities, face, genitals, bowels, and upper airways. AE is commonly misdiagnosed due to restricted access and availability of appropriate laboratorial tests. HAE with C1 inhibitor defect is associated with quantitative and/or functional deficiency. Although bradykinin-mediated disease results mainly from disturbance in the kallikrein-kinin system, traditionally complement evaluation has been used for diagnosis. Diagnosis is established by nephelometry, turbidimetry or radial immunodiffusion for quantitative measurement of C1 inhibitor and chromogenic assay or ELISA have been used for functional C1-INH analysis. Wrong handling of the samples can lead to misdiagnosis and, consequently, mistaken inappropriate approaches. Dried blood spot (DBS) tests have been used for decades in newborn screening for certain metabolic diseases, and there has been growing interest in their use for other congenital conditions. Recently, DBS is now proposed as an efficient tool to diagnose HAE with C1 inhibitor deficiency, and its use would improve the access to outbound areas and family members. Regarding HAE with normal C1 inhibitor, complement assays’ results are normal and the genetic sequencing of target genes, such as exon 9 of F12 and PLG, is the only available method. New methods to measure cleaved high molecular weight kininogen and activated plasma kallikrein have emerged as potential biochemical tests to identify bradykinin-mediated angioedema. Validated biomarkers of kallikrein-kinin system activation could be helpful in differentiating mechanisms of angioedema. Our aim is to focus on the capability to differentiate histaminergic AE from bradykinin-mediated AE. In addition, we will describe the challenges developing specific tests like direct bradykinin measurements. The need for quality tests to improve the diagnosis, is well represented by the variability of results in functional assays.